New taxa of the subtribe Lebinthina (Orthoptera: Gryllidae: Eneopterinae: Lebinthini) from New Guinea and nearby islands - Tan, Ming Kai; Robillard, Tony (Zootaxa, 2021)
Four new species from three genera of Lebinthina crickets are described here. These include one species of Gnominthus: Gnominthus milneus sp. nov. from Papua New Guinea; two new species of Macrobinthus: Macrobinthus kei sp. nov. and Macrobinthus mamai sp. nov. from Maluka (Indonesia) and Papua New Guinea, respectively; and one species of Microbinthus: Microbinthus elegans sp. nov. from Papua New Guinea.